Bauran Pemasaran Beras Shirataki di Toko Beras Sehat Bali - Kadek Ayu Charisma Julia Dewi; Ni Ketut Karyati; Made Mika Mega Astuthi (CV. Ulil Albab Corp, 2024)
Shirataki rice is rice made from porang tubers. Porang bulbs are plants that produce carbohydrates, fats, proteins, minerals, which can be processed into shirataki rice. Shirataki rice has many benefits for the body such as preventing an increase in blood sugar levels and improving the health of the digestive tract. In order to find out how the process of marketing shirataki rice is, it is necessary to do research on the mix of shirataki rice and the marketing constraints of Shirataki rice. The research location was determined purposively or purposively with the consideration that the Beras Sehat Bali store is in a very strategic location close to tourism and has been running for more than 10 years. The population in this study amounted to 11 people consisting of leaders and employees. By paying attention to the small number of population, this study used a census technique , namely taking the entire population as a research unit. The data analysis method used is descriptive analysis. The results of this study are that the product marketed by the Satvika Bhoga Shop is Shirataki Rice with the KONNYAKU brand, with packaging measuring 250 gr and 1 kg. The marketing price for Shirataki rice products, which are 250 grams in size, is Rp 95,000 and 1 kg in size is Rp 225,000. The location of the Satvika Bhoga Store is very strategic, close to tourism sites, and is also located on the side of the main road, so that it is easy for consumers to reach. Product promotion is carried out in 2 ways, namely direct promotion and through social media (Instagram, Facebook, WhatsAAP, WebSite). The constraints faced are sometimes a shortage of stock, due to the shirataki rice production process in Surabaya.